The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1515/ijdhd.2007.6.4.383
|View full text |Cite
|
Sign up to set email alerts
|

Fetal alcohol spectrum disorders and mental illness

Abstract: Objective: To discuss relevant issues in the diagnosis of mental disorders comorbid with fetal alcohol spectrum disorders (FASD). Methods: We present a theoretical model of the effect of prenatal alcohol exposure on neurobehavioral development and a systematic review of published data on the mental disorders in subjects with an FASD. Results: Prenatal alcohol exposure is associated with high rates of mental disorders. We found 48 papers reporting on 3,343 subjects. The most common mental disorder comorbid with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 16 publications
(17 reference statements)
0
14
0
Order By: Relevance
“…Numerous studies have found individuals with FASDs to be at elevated risk for disruptive behavior problems, mood disorders, substance use or abuse problems, and psychiatric confinement [Famy et al, 1998;O'Connor et al, 2002;Burd et al, 2003;Streissguth et al, 2004;Bhatara et al, 2006;Burd et al, 2007;Walthall et al, 2008]. Given such findings, it is not surprising that children with FASDs often receive pharmacological intervention.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…Numerous studies have found individuals with FASDs to be at elevated risk for disruptive behavior problems, mood disorders, substance use or abuse problems, and psychiatric confinement [Famy et al, 1998;O'Connor et al, 2002;Burd et al, 2003;Streissguth et al, 2004;Bhatara et al, 2006;Burd et al, 2007;Walthall et al, 2008]. Given such findings, it is not surprising that children with FASDs often receive pharmacological intervention.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…FASD may be as prevalent as 1% of live births and the affected person has increased risk for a wide range of mental disorders and social impairments that differ over the lifespan (Burd et al, 2007a;Sampson et al, 1997;Streissguth et al, 2004). The disorder is recurrent and the incidence of the disorder among siblings of those diagnosed with fetal alcohol syndrome (FAS) ranges from 170 per 1,000 for older siblings to 771 per 1,000 for younger siblings, making FASD both one of the most recurrent and most preventable developmental disorders (Abel, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Early detection of infants with prenatal alcohol exposure (PAE) combined with close monitoring of developmental progress may provide early access to intervention during an optimal time period to maximize developmental potential (Burd, 2006). Early diagnosis and intervention may also have an important role in prevention of secondary disabilities (Burd et al, 2007a;Streissguth et al, 2004). Mothers of a child diagnosed with an FASD are in urgent need of substance abuse treatment to prevent recurrence of FASD in subsequent pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Although attention deficits among children with FASDs are well documented in the literature and corroborate the widespread presence of these problems in children with PAE [39][40][41], investigators have suggested that while they may share common features, the inattention and hyperactivity associated with PAE denote a particular clinical subtype with an earlier onset, a different clinical and neuropsychological presentation, and probably a differential medication response than idiopathic ADHD [3•, 39, 42]. Significantly, results reported from three large population-based pregnancy offspring cohorts within the Nordic Network on ADHD found that PAE was not related to risk for ADHD after adjustment for covariates [43].…”
Section: Middle Childhoodmentioning
confidence: 78%